Ultracentrifugation of Acetylated Thrombin - Seegers, Walter H.; Shepard, Robert S.; Landaburu, Ricardo H. (Thrombosis and Haemostasis, 1960)
Acetylated bovine thrombin with a specific activity of 5930 units per milligram dry weight was found to be homogeneous by ultracentrifuge analysis. The sedimentation constant in units of 10−13 sec. at 20° C, in 0.1 M potassium chloride was 3.3. This constant is not concentration dependent.